Love blooms - McNally, Jo (McNally, Jo. Rendezvous Falls, 2021)
When his fiancé runs out on him, Owen Cooper follows her to Rendezvous Falls where he refuses to let her go without a fight as he tries to convince her that he's finally and truly ready to let her into his heart.